ANALYSIS OF RICE PRODUCTION APPROACH TO COBB DOUGLAS PRODUCTION FUNCTION IN TAMBAKDAHAN SUB-DISTRICT SUBANG DISTRICT - Tete Saepudin; Anita Amalia (Agricultural Socio-Economics Journal, 2022)
Rice production is still the primary source of livelihood for rural communities in Tambakdahan Sub-district, Subang Regency. One harvest of every hectare can produce an average rice production of 8.5 to 9 tons. This study aims to determine the effect of land area ownership, use of labor, use of seeds, fertilizers, and technical irrigation (irrigation) on rice production and the Scale of business results, using the Cobb Douglas production function equation. The results of this study indicate that the three input variables have significant influence, namely; ownership of land area, fertilizers used, and technical irrigation (irrigation) on rice production, for the use of seed input, and technical irrigation (irrigation) have a positive effect, while the input of land area ownership has a negative impact. Two input variables do not have a significant effect, namely the input use of labor and seeds. The Scale of the results of the rice production business shows a decreasing scale of business results